Pemikiran Pendidikan Akhlak Ibnu Maskawaih dan Relevansinya dalam Pendidikan Akhlak di MTs Islamiyah Kepung - Ahmad Masrukin; Nila Nur Hikmah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
Ibnu Maskawaih is an intellectual in the field of moral philosophy. Ibn Maskawaih's moral philosophy thoughts do not hinder them and may even be able to provide motivation and great influence for the existence of renewal thoughts in Islam, especially in moral education. Based on the thoughts above, the author considers that it is important to study the title "Ibn Maskawaih's Thoughts on Moral Education and Its Relevance in Moral Education at Mts Islamiyah Kepung", so this research will discuss the thoughts of Ibnu Maskawaih and their relevance to moral education at Mts Islamiyah Kepung, this research aims to determine the implementation of Ibn Maskawaih's moral education at MTs Islamiyah Kepung and to determine the relevance and impact of moral education at MTs Islamiyah Kepung. This research uses a qualitative descriptive method with descriptive analysis techniques as well. In the process of collecting data, the authors used observation, interviews and documentation, the results of the study showed that some of the methods proposed by Ibnu Maskawaih were relevant for use in formal education such as at MTs Islamiyah and implemented in daily teaching and learning activities (KBM) especially in lessons The Akhlak Aqidah which of course contains lessons about morals, conclusions.moral education. The purpose of moral education is implemented in MTs by providing materials and methods that can mold students into pious and morally good people. The impact of moral education on students is to make students who can be emulated and become good role models or have noble character. and have good manners.